2005
DOI: 10.1016/j.jacc.2005.08.033
|View full text |Cite
|
Sign up to set email alerts
|

Cost Effectiveness of Cardiac Resynchronization Therapy in the Comparison of Medical Therapy, Pacing, and Defibrillation in Heart Failure (COMPANION) Trial

Abstract: For the COMPANION trial patients, the use of CRT-P and CRT-D was associated with a cost-effectiveness ratio below generally accepted benchmarks for therapeutic interventions of 50,000 dollars per QALY to 100,000 dollars per QALY. This suggests that the clinical benefits of CRT-P and CRT-D can be achieved at a reasonable cost.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
81
0
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 165 publications
(87 citation statements)
references
References 29 publications
(23 reference statements)
3
81
0
3
Order By: Relevance
“…Inclusion criteria included NYHA functional class III or IV plus a HF treatment in the preceding 12 months over and above other criteria. The ICERs for CRT‐P and CRT‐D vs. optimal medical therapy were US$19 600 and US$43 000, respectively, over a 7‐year time horizon 44. Using the CPI for medical care inflation of an average of 4.03%, the ICER for CRT‐P vs. optimal medical therapy and CRT‐D vs. optimal medical therapy would be US$27 513/QALY and US$60 360/QALY, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Inclusion criteria included NYHA functional class III or IV plus a HF treatment in the preceding 12 months over and above other criteria. The ICERs for CRT‐P and CRT‐D vs. optimal medical therapy were US$19 600 and US$43 000, respectively, over a 7‐year time horizon 44. Using the CPI for medical care inflation of an average of 4.03%, the ICER for CRT‐P vs. optimal medical therapy and CRT‐D vs. optimal medical therapy would be US$27 513/QALY and US$60 360/QALY, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Analyses of controlled trials have shown the time dependency of the beneficial effects of ICDs on mortality, with a lack of benefit in the first months after implantation and an exponential rise in benefit thereafter reaching a peak after 3 years [65]. Accordingly, economic analyses have shown that it may need up to 6-7 years of follow-up to be cost effective [66,67]. Thus, ICDs may not be indicated in patients with ACHF and a predicted short life expectancy.…”
Section: Implantable Cardioverter Defibrillator (Icd)mentioning
confidence: 99%
“…These figures are well within the benchmark of 50 000 USD per QALY gained that has been used to delineate the upper margin for cost-effective healthcare interventions in the USA, and similar thresholds that are accepted in Europe. By contrast, the costeffectiveness of using CRT-D instead of CRT-P is difficult to determine, given the limited data available, but has been estimated as 43 000 USD per QALY and 46 700 USD per life-year gained based on data from the COMPANION study [69]. In the REVERSE trial, CRT was found to be cost-effective at 14 278 EURO per QALY gained, indicating that this therapy is a cost-effective intervention even for patients with mildly symptomatic HF [70].…”
Section: Cost-effectivenessmentioning
confidence: 99%